2021
DOI: 10.1080/21655979.2021.1872191
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0001287 inhibits the proliferation, metastasis, and radiosensitivity of non-small cell lung cancer cells by sponging microRNA miR-21 and up-regulating phosphatase and tensin homolog expression

Abstract: As a type of non-coding RNA, circular RNA (circRNA) figures prominently in human cancer progression. Nonetheless, the expression, function, and regulatory mechanism of circ_0001287 in non-small cell lung cancer (NSCLC) remain obscure. In this work, quantitative real-time polymerase chain reaction (qRT-PCR) was implemented to quantify circ_0001287 and miR-21 expressions in NSCLC tissues and cells. The relationship between circ_0001287 expression and the clinicopathological parameters of NSCLC patients was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…For example, circ_0001287 can reduce radiotherapy resistance, thus providing new clues for the treatment of lung cancer. 136 Therefore, circRNAs are closely related to the solution of radiotherapy resistance.…”
Section: Circrnas In Lung Cancermentioning
confidence: 99%
“…For example, circ_0001287 can reduce radiotherapy resistance, thus providing new clues for the treatment of lung cancer. 136 Therefore, circRNAs are closely related to the solution of radiotherapy resistance.…”
Section: Circrnas In Lung Cancermentioning
confidence: 99%
“…More and more studies have shown that non-coding RNA plays a key role in a variety of human diseases, such as circRNA can directly participate in the regulation of cell proliferation, differentiation, migration and invasion by activating a variety of signaling pathways, thus playing an important role in the occurrence and development of malignant tumors. [8][9][10][11][12][13] and a variety of circular RNAs play an important regulatory role in the proliferation, invasion and metastasis of lung cancer cells. [14][15][16] Studies have shown that circPTCH1 is related to the occurrence and development of tumor, participates in the formation, invasion and metastasis of tumor, and may play the role of oncogene in tumor, 17 but the mechanism of circPTCH1 in lung cancer is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 15 One recent study by Zhang and his colleagues showed that circular RNA circ_0001287 inhibited the proliferation, metastasis, and radiosensitivity of non‐small cell lung cancer cells by sponging miR‐21. 16 Hao et al reported that circDCUN1D4 suppressed tumor metastasis and glycolysis in lung adenocarcinoma by stabilizing TXNIP expression. Additionally, due to its characteristics of abundance, diversity, stability, and disease‐specific exhibition, circRNA was considered as ideal biomarker for auxiliary diagnosis and prognosis estimation of disease.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 One recent study by Zhang and his colleagues showed that circular RNA circ_0001287 inhibited the proliferation, metastasis, and radiosensitivity of non-small cell lung cancer cells by sponging miR-21. 16 Hao et al reported that circDCUN1D4 suppressed tumor metastasis and glycolysis in lung adenocarcinoma by stabilizing TXNIP expression.…”
mentioning
confidence: 99%